Connatal Urinary Ascites in a Female Preterm - Barbara Brunner; Elisabeth Ralser; Elisabeth D’Costa; Kathrin Maurer; Ursula Kiechl-Kohlendorfer; Elke Griesmaier (Case Reports in Pediatrics)
Background. Connatal urinary ascites is rare in females without associated malformations and occurs following bladder rupture. Case Presentation. A female very preterm was delivered by caesarean section because of abnormal Doppler findings. The mother suffered from viral pneumonia requiring intensive care in the third trimester of pregnancy. Serial fetal ultrasound examinations showed a megacystis and ascites. Postnatally, pronounced isolated ascites was drained and its urinary nature was confirmed. The bladder leak was demonstrated when blue dye, instilled via a Foley catheter, appeared in the ascitic drain. After removal of the catheter spontaneous micturition was unremarkable. A micturating cystourethrogram showed spontaneous closure of the bladder leak. Conclusion. The female infant experienced fetal bladder rupture and connatal urinary ascites due to maternal pneumonia and intensive care. The use of blue dye is an effective alternative method to any contrast media radiography and should be considered, especially in very preterm infants.